The pas8 mutant of Pichia pastoris exhibits the peroxisomal protein import deficiencies of Zellweger syndrome cells--the PAS8 protein binds to the COOH-terminal tripeptide peroxisomal targeting signal, and is a member of the TPR protein family [published erratum appears in J Cell Biol 1993 Sep;122(5):following 1143] (The Rockefeller University Press, 1993)
We previously described the isolation of mutants of the yeast Pichia pastoris that are deficient in peroxisome assembly (pas mutants). We describe the characterization of one of these mutants, pas8, and the cloning of the PAS8 gene. The pas8 mutant is deficient for growth, but not for division or segregation of peroxisomes, or for induction of peroxisomal proteins. Two distinct peroxisomal targeting signals, PTS1 and PTS2, have been identified that are sufficient to direct proteins to the peroxisomal matrix. We show that the pas8 mutant is deficient in the import of proteins with the PTS1, but not the PTS2, targeting signal. This is the same import deficiency as that found in cells from patients with the lethal human peroxisomal disorder Zellweger syndrome. Cloning and sequencing of the PAS8 gene reveals that it is a novel member of the tetratricopeptide repeat gene family. Antibodies raised against bacterially expressed PAS8 are used to show that PAS8 is a peroxisomal, membrane-associated protein. Also, we have found that in vitro translated PAS8 protein is capable of binding the PTS1 targeting signal specifically, raising the possibility that PAS8 is a PTS1 receptor.